2009
DOI: 10.1016/j.virol.2008.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Non-virulence of a recombinant shrimp nidovirus is associated with its non structural gene sequence and not a large structural gene deletion

Abstract: RT-PCR using a commercial kit for yellow head virus (YHV) detection in growth-retarded shrimp yielded an unusual 777 bp amplicon instead of expected amplicons of 277 bp for YHV type-1 (YHV-1) or 406 bp for YHV type-2 (YHV-2). Cloning and sequencing (GenBank EU170438) revealed approximately 80% identity to non-structural (NS) ORF1b sequences of both YHV-1 (GenBank AA083987) and YHV-2 (GenBank AF227196), indicating an atypical YHV type (A-YHV) phylogenetically equidistant from both types. An RT-PCR test specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Most sequence diversity, including block insertions/deletions, occurs near to the gp116 N terminus, generated by cleavage at a signal peptidase type 1 site at TM domain 3 of the ORF3 polyprotein. Two YHV genotype 1 variants from Thailand, one virulent (genotype 1b) (Sittidilokratna et al, 2009) and the other non-virulent (A-YHV) (Gangnonngiw et al, 2009), for which sequence data have been reported recently, both possess a 54 aa deletion in the gp116 Nterminal region that eliminates the N 63 TS and N 44 ST sites, found here to be glycosylated in the YHV genotype 1a strain. Despite sequence differences and the loss of these two glycan-linked sites in gp116 of YHV genotype 1b strains, they retain virulence, albeit somewhat reduced compared with genotype 1a strains (Sittidilokratna et al, 2009).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Most sequence diversity, including block insertions/deletions, occurs near to the gp116 N terminus, generated by cleavage at a signal peptidase type 1 site at TM domain 3 of the ORF3 polyprotein. Two YHV genotype 1 variants from Thailand, one virulent (genotype 1b) (Sittidilokratna et al, 2009) and the other non-virulent (A-YHV) (Gangnonngiw et al, 2009), for which sequence data have been reported recently, both possess a 54 aa deletion in the gp116 Nterminal region that eliminates the N 63 TS and N 44 ST sites, found here to be glycosylated in the YHV genotype 1a strain. Despite sequence differences and the loss of these two glycan-linked sites in gp116 of YHV genotype 1b strains, they retain virulence, albeit somewhat reduced compared with genotype 1a strains (Sittidilokratna et al, 2009).…”
Section: Discussionmentioning
confidence: 58%
“…Of the three YHV structural proteins, the amino acid sequence of gp116 is most variable amongst the genotypic variants (Gangnonngiw et al, 2009;Sittidilokratna et al, 2009;Wijegoonawardane et al, 2008). Most sequence diversity, including block insertions/deletions, occurs near to the gp116 N terminus, generated by cleavage at a signal peptidase type 1 site at TM domain 3 of the ORF3 polyprotein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of an RT-PCR amplicon and no nested PCR amplicons, as was the case for YHV7, has occurred previously with a YHV1b/YHV5 recombinant virus (Gangnonngiw et al 2009). A similar result has also been observed for an, as yet, unassigned yellow-head-complex virus detected in several provinces of China (Liu et al 2014).…”
Section: Discussionmentioning
confidence: 79%
“…As with other members of the order Nidovirales , these viruses have a linear positive-sense ssRNA genome encoding a large replicase polyprotein that is expressed from the genomic RNA (ORF1a and, via ribosomal frameshifting, an ORF1a-ORF1b fusion product), and a number of other proteins - including the structural proteins - which are translated from a nested set of 3'-coterminal sub-genomic RNAs [1-4]. In the case of the okaviruses, the 3' ORFs encode a polyprotein (ORF3; ~1650 codons) that is cleaved to produce three mature proteins (envelope glycoproteins gp116 and gp64, and an ~25 kDa N-terminal fragment), a nucleocapsid (ORF2; ~145 codons), and possibly an additional short ORF (ORF4) encoded by the sequence 3' of ORF3 (Figure 1A) [4-10]. …”
Section: Resultsmentioning
confidence: 99%